Digitalisasi Profil Usaha UMKM Desa Mondo melalui Pembuatan dan Pengelolaan Listing Google Maps - Rahmawan, Miftah Nur; Asy’ari, Nabil Asy’ari; Prakoso, Bagus Tegar; Ashara, Mei Fajar; Gymnastiar, Asrofi Wildan; Romadhoni, Mochamad Daud; Zakiyati, Husna Naila; Rahmawati, Amanda; Mayasari, Anita Yulia; Fadillah, Nadia Nur; Kummairoh, Sinta Haniatul; Rosyidah, Nur Fadlilatur; et al. (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) is a concrete form of student community service organized by universities. Through this activity, students go directly into the field to make a positive contribution to the surrounding environment, particularly in helping develop village potential. The development of digital technology has opened up new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their market reach. One effective strategy is using Google Maps to list and promote business locations. This study aims to identify and analyze strategies for increasing the visibility of MSME products in Mondo Village by including business information on Google Maps. The method used is a qualitative descriptive approach with data collection through interviews, field observations, and documentation. The results show that including business locations and profiles on Google Maps significantly makes it easier for consumers to identify products, increases the number of visits, and strengthens the business's image in the eyes of customers.